On the Solution of a Singular Cauchy Problem for a First-Order Differential Equation Unsolved with Respect to the Derivative of an Unknown Function - Zernov, A. E. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For a first-order ordinary differential equation, we establish conditions under which a singular Cauchy problem has a unique continuously differentiable solution with required asymptotic behavior.